Serum salusin-alpha level in rheumatoid arthritis - Ozgen, Metin; Koca, Suleyman Serdar; Dagli, Necati; Balin, Mehmet; Ustundag, Bilal; Isik, Ahmet (Elsevier, 2011)
Rheumatoid arthritis (RA), a chronic inflammatory disease, leads to early and accelerated atherosclerosis; however, its pathogenesis is not yet fully documented. Salusin-alpha and beta are novel bioactive peptides. Salusin-alpha suppresses macrophage foam cell formation, while salusin-beta stimulates. Moreover, decreased serum salusin-alpha level has been reported previously in patients with coronaryartery disease. The aims of the study were to assess serum salusin-a level and its association with predictors of atherosclerosis in a cohort of patients with RA. The study included 56 RA patients, 37 Behcet's disease (BD) patients, and 29 healthy controls (HC).TNF-alpha, IL-6 and salusin-a levels, homeostasis model assessment (HOMA-IR) index and common carotid intima-media thickness (IMT) were determined. In the RA and BD groups, salusin-alpha levels (p < 0.001 and p < 0.01, respectively) and IMTs (p < 0.001 for both) were higher compared to the HC group. However, the level of salusin-alpha was not directly associated with the IMT in all the groups. Serum salusin-alpha levels are increased in RA and BD, although they have increased IMT. Salusin-alpha has been reported to have anti-atherogenic effects in previous studies. However, it seems that salusin-alpha does not directly affect the atherogenesis in RA and BD. Further studies are needed to understand the regulation of salusin-alpha and determination of its relations with the predictors of atherosclerosis in RA and BD. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Salusin-alpha; Atherosclerosis; Rheumatoid arthritis; Behcet's disease